Time-resolved observation of transient precursor state of CO on Ru(0001) using carbon K-edge spectroscopy. Issue 5 (18th September 2019) - Wang, Hsin-Yi; Schreck, Simon; Weston, Matthew; Liu, Chang; Ogasawara, Hirohito; LaRue, Jerry; Perakis, Fivos; Dell'Angela, Martina; Capotondi, Flavio; Giannessi, Luca; Pedersoli, Emanuele; Naumenko, Denys; et al.
Abstract : The transient dynamics of carbon monoxide (CO) molecules on a Ru(0001) surface following femtosecond optical laser pump excitation has been studied by monitoring changes in the unoccupied electronic structure using an ultrafast X-ray free-electron laser (FEL) probe. Abstract : The transient dynamics of carbon monoxide (CO) molecules on a Ru(0001) surface following femtosecond optical laser pump excitation has been studied by monitoring changes in the unoccupied electronic structure using an ultrafast X-ray free-electron laser (FEL) probe. The particular symmetry of perpendicularly chemisorbed CO on the surface is exploited to investigate how the molecular orientation changes with time by varying the polarization of the FEL pulses. The time evolution of spectral features corresponding to the desorption precursor state was well distinguished due to the narrow line-width of the C K-edge in the X-ray absorption (XA) spectrum, illustrating that CO molecules in the precursor state rotated freely and resided on the surface for several picoseconds. Most of the CO molecules trapped in the precursor state ultimately cooled back down to the chemisorbed state, while we estimate that ∼14.5 ± 4.9% of the molecules in the precursor state desorbed into the gas phase. It was also observed that chemisorbed CO molecules diffused over the metal surface from on-top sites toward highly coordinated sites. In addition, a new "vibrationally hot precursor" state was identified in the polarization-dependent XA spectra.